The predictive ability of cultural intelligence in happiness among Ajman University students - Alzoubi, Ahmad; Abdellah, Rasha (Dirasat: Human and Social Sciences, 2021)
The study aimsat identifying the relationship between cultural intelligence and happiness among Ajman University students in the light of sex and specialization. The study sample consisted of 282 students at Ajman University. Cultural intelligence scale and Oxford Happiness scale were applied in this study. The results did not find significant differences in the total cultural intelligence, its dimensions and the happiness due to sex and specialization, except for the significant differences in the behavioral dimension attributed to specialization for the benefit of humanities faculties. The study showed significant positive relationships between cultural intelligence with happiness; as simple regression results indicated that total cultural intelligence predicted a degree of happiness (R Square= .24), and the stepwise multiple regression analysis also revealed that the metacognitive, motivational, and behavioral dimensions of cultural intelligence predicted a degree of happiness (R Square= .27). Finally, the study recommended the need to integrate the dimensions and skills of cultural intelligence into programs and activities aim at promoting happiness among Ajman University students.